Atypically mitral valve originated giant myxoma presenting with acute ST-segment elevation myocardial infarction and acute pulmonary edema - Demirdaş, Ertan; Atılgan, Kıvanç; Er, Zafer Cengiz; Çiçekçioğlu, Ferit (Journal of Surgery and Medicine, 2018)
Cardiac myxoma is a rare disease with an incidence of 0.0017-0.03%, and most frequently are seen between the third and sixth decades. The 65% of cases are female. They originate from left atrium in 75% of the cases, from right atrium in 18% and from ventricles in 4%. The most rarely seen cardiac origins are valvular tissues and respectively origin from tricuspid valve, mitral valve, pulmonary valve and aortic valve. The exact incidence of myxomas originating from the mitral valve is not clear. Clinical signs are classified in three groups such as systemic symptoms, symptoms related to thromboembolisms and symptoms related to intracardiac obstructions. Weakness, fever, weight loss, arthralgia are some of the systemic symptoms. Thromboembolisms are caused by either the tumoral tissue or the clot locating on the mass. Dyspnea, orthopnea, dizziness, syncope and pulmonary edema are examples of symptoms resulting from intracardiac obstructions, depending on the size, mobility and localization of the tumor. We aim to present a 77-year-old female presenting with dyspnea, angina pectoris and tachycardia and getting a diagnosis of a giant myxoma originating from the mitral annulus and posterior leaflet causing myocardial infarction with ST elevation, acute pulmonary edema, pulmonary hypertension, paroxysmal atrial fibrillation.